Earmarking for global health: benefits and perils of the World Bank's trust fund model. (31st August 2017) - Winters, Janelle; Sridhar, Devi
Abstract : In the third article in this series, Janelle Winters and Devi Sridhar review different types of trust funds and how they fit within the bank's lending mechanism, and discuss the major benefits and risks of the bank's use of the trust fund model for health